HER MENEUTIKA HADIS FATIMA MERNISSI (Aplikasi terhadap Hadis Kepemimpinan Perempuan) - Kholila Mukaromah (IAIN Kediri, 2018)
The use of hermeneutic as one of approaches in hadith study becomes one of knowledge integration forms which is implemented in the contemporary era. The knowledge integration between hadith and hermeneutic can be found such as from a study conducted by Fatima Mernissi. The Mernissi’s concept toward the issue of gender equality has brought her to study hadith that as if support the views lowering women (misogyny). Based on that argument, this article tries to explore more descriptivelyanalytic about the form of hermeneutic hadith of Fatima Mernissi in her effort in understanding misogyny hadith. The research problems are how is Fatima Mernissi’s thought related to the Prophet’s hadith from the rising and process of its collecting?, how is Mernissi’ hermeneutic hadith form that is showed through double investigation methods? How is the description of the method application in Abu Bakrah’s riwayah about women leadership?. This study is a literature study, and its discussion is more descriptive-analytic. Based on her, method in hadith knowledge that has been shown by the classic scholars (ulama) should be completed by the development of contemporary knowledge that puts scientific aspect as the more important aspect than normative aspect. Keywords: Hermeneutic, Hadith, Fatima Mernissi, women leadership